Largo Caballero (note)
LARGO CABALLERO There was a statement in the "New York Nation" to the effect that Caballero was still in France but that he had a visa for Mexico which he could not at present use because the only way out of France was over Spain. It was stated that the Vichy Government had given an assurance to Washington that Caballero would not be handed over to the Franco Government We wrote to Lord Halifax when we thought Caballero was in Franco's hands and he said there was little hope of intervention on the Ambassador's part being successful. Mr. Tewson and the Chairman made statements to the December meeting of the General Council in which they expressed the inadvisability of our becoming too openly associated with requests to the Spanish Government for the release of Caballero. Mr. Stoltz is making enquiries of certain Spanish friends and will let us have some more information as soon as he gets it tomorrow. 292/946/13/49(i)